Abdominal intra-compartment syndrome – a non-hydraulic model of abdominal compartment syndrome due to post-hepatectomy hemorrhage in a man with a localized frozen abdomen due to extensive adhesions: a case report. (December 2016) - Bressan, Alexsander; Kirkpatrick, Andrew; Ball, Chad
Abstract Background Postoperative hemorrhage is a significant cause of morbidity and mortality following liver resection. It typically presents early within the postoperative period, and conservative management is possible in the majority of cases. We present a case of late post-hepatectomy hemorrhage associated with overt abdominal compartment syndrome resulting from a localized functional compartment within the abdomen. Case presentation A 68-year-old white man was readmitted with sudden onset of upper abdominal pain, vomiting, and hemodynamic instability 8 days after an uneventful hepatic resection for metachronous colon cancer metastasis. A frozen abdomen with adhesions due to complicated previous abdominal surgeries was encountered at the first intervention, but the surgery itself and initial recovery were otherwise unremarkable. Prompt response to fluid resuscitation at admission was followed by a computed tomography of his abdomen that revealed active arterial hemorrhage in the liver resection site and hemoperitoneum (estimated volume <2 L). Selective arteriography successfully identified and embolized a small bleeding branch of his right hepatic artery. He remained hemodynamically stable, but eventually developed overt abdominal compartment syndrome. Surgical exploration confirmed a small volume of ascites and blood clots (1.2 L) under significant pressure in his supramesocolic region, restricted by his frozen lower abdomen, which we evacuated. Dramatic improvement in his ventilatory pressure was immediate. His abdomen was left open and a negative pressure device was placed for temporary abdominal closure. The fascia was formally closed after 48 hours. He was discharged home at postoperative day 6. Conclusions Intra-abdominal pressure and radiologic findings of intra-abdominal hemorrhage should be carefully interpreted in patients with extensive intra-abdominal adhesions. A high index of suspicion and detailed understanding of abdominal compartment mechanics are paramount for the timely diagnosis of abdominal compartment syndrome in these patients. Clinicians should be aware that abnormal anatomy (such as adhesions) coupled with localized pathophysiology (such as hemorrhage) can create a so-named abdominal intra-compartment syndrome requiring extra vigilance to diagnose.